Antineoplastic mechanism of gemcitabine on tumor cells with different TP53/p53 subtypes - da Silva, Glenda Nicioli; Salvadori, Daisy Maria Favero [UNESP] (My University, 2014)
The aim of this chapter is to provide updated information on the mechanisms by which gemcitabine acts on tumor cells with different TP53 gene backgrounds. Currently, the genetic backgrounds of tumors and patients have been taken into account to ensure efficient treatment. In this context, the TP53 gene status has been shown to play a pivotal role in the action of a large panel of antitumor agents, and several mutations have been found to confer new functions to the mutant p53 protein, which interferes in the treatment response. Among the antitumor drugs that are currently used in chemotherapy, gemcitabine has been demonstrated to be one of the most promising due to its lower toxicity and good tolerability. This compound is a pyrimidine nucleoside antimetabolite agent that is effective against a variety of human malignancies, including tumors of non small cell lung, bladder, breast, pancreas, ovarian and others. Although the relationship between gemcitabine treatment success and the TP53/p53 status has been poorly investigated, it is known that the p53 protein recognizes gemcitabine after it has been incorporated into the cell. The literature has described that when administered alone, the effects of gemcitabine are independent of the TP53/p53 status; however, different pathways are activated for each tumor type. Some data support that when administered with other antineoplastic drugs or radiotherapy, the TP53/p53 status is important for gemcitabine cytotoxicity.